Character Education Based on Javanese Cultural Values in Madrasah Aliyah Al Islam Surakarta, MAN 2 Semarang, and Madrasah Aliyah Al Manshur Popongan - Murjito, Joko; Siregar, Maragustam; Mulyo, Mufrod Teguh (Program Studi Pendidikan Agama Islam, 2022)
This study aims to analyze the importance of character education based on Javanese cultural values and the implementation of character education construction based on Javanese cultural values. The objects of this research were Madrasah Aliyah Al Islam Surakarta, MAN 2 Semarang, and Madrasah Aliyah Al Manshur Popongan. In its implementation, qualitative research was used with phenomenological and naturalistic approaches. Data collection techniques were through observation, interviews, and documentation. The discussion in this article leads to the conclusion that Javanese culture is vital since it can be used as a medium and means of forming students' character, containing the fundamental beliefs and knowledge sources in harmony with Islamic teachings. The implementation process is through the construction of approaches, values, methods, media, strategies, and evaluations reflected in the 2013 curriculum and Central Java Regional Regulation Number 9 of 2012, which are integrated into every subject, extracurricular activities, school culture, habituation and exemplary, and school regulations.